The Role of Vascular-Platelet Hemostasis Disturbances in the Genesis of Respiratory Failure in Patients with COVID-19 - M. I. Neymark; D. P. Epp; M. G. Nikolaeva; A. P. Momot; S. N. Proskurin; A. N. Karkavina; V. V. Kontseba; C. V. Mekshun (Вестник анестезиологии и реаниматологии, 2022)
The objective: to study the relationship between markers of imbalance in the platelet-vascular hemostasis system and lung damage and disease outcome in patients with COVID-19.Subjects and Methods: the study included 225 patients with the confirmed diagnosis of moderate, severe and extremely severe COVID-19. In all patients, lung damage was confirmed using computed and X-ray diagnostic methods. We studied the concentration of von Willebrand factor (vWF), activity of metalloproteinase ADAMTS-13, concentration of homocysteine, endothelin-1, thrombomodulin and the number of platelets and changes in these parameters on the 1st, 3–5th and 7–10th days from the admission to the intensive care unit (ICU). In deceased patients (n = 106), lung specimens were collected to assess the nature of morphological changes.Results. It was determined that by the 7–10th days with a lethal outcome of the disease, there was a statistically significant increase in the concentration of vWF by 22.2% (p = 0.0225), the vWF/ADAMTS-13 ratio by 2 times (p = 0.0408) and decrease in the platelet count by 52% (p = 0.0008) versus the initial stage of the study. In all the deceased, the morphological picture of lung tissue damage was characterized by destruction of alveolocytes, proliferation of connective tissue, cellular infiltration, plethora of capillaries, parietal erythrocyte thrombi in the lumen of capillaries, arterioles and venules, and obstructive erythrocyte thrombi in the lumen of vessels of lung microcirculation.Conclusion. The study showed that a possible cause of thrombosis in the lumen of vessels of lung microcirculation in the case of a lethal outcome of COVID-19 might be a primary imbalance in the vascular-platelet hemostasis characterized by a significant increase in the concentration of the vWF factor, the vWF/ADAMTS-13 ratio and a decrease in the number (consumption) of platelets by the 7–10th day of the disease versus the initial stage of the study.